MODEL BARU PENGGUNAAN SMARTPHONE UNTUK ALAT PENGERING GABAH (PADI) DENGAN PENGATURAN SUHU PANAS BERBASIS ARDUINO UNO - Zulkarnain, Zulkarnain; Aryza, Solly (Scenario (Seminar of Social Sciences Engineering and Humaniora); 2023, 2023)
Android is an operating system for Linux-based mobile phones. Android provides an open platform for developers to create their own applications for use by various devices, the purpose of this research is to produce real results in providing comfort or convenience in controlling the daily grain (rice) dryer without touching the controller igniter button, especially for people with physical disabilities or elderly people who are difficult to stand. In making this research turn on the igniter button of the heating device with arduino uno-based voice commands using a smartphone. The results achieved are improving aspects of comfort and convenience for people with physical disabilities or the elderly, who find it difficult to stand or reach the tool switch, where this tool can work after the bluetooth device is available on the android smartphone. Basically the principle of using this tool the user must be able to operate a smartphone based on the android operating system.